(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This study explores the enhancement of VTM (Vertical Tube Module) type fiber cleaning equipment, widely utilized in foreign technology, through an increase in the number of columns. The objective is to extend the fiber splitting time and improve cleaning efficiency. The impurities found in cotton fibers are classified as active and passive, originating from mineral and organic sources, as well as impurities in seeded cotton. These impurities, introduced during the ginning process, significantly impact fiber quality. In textile factories, residual impurities such as large and small debris, crushed seeds, pulp, fibrous shells, and other contaminants affect the quality of the fiber. Moreover, the formation of coils during the fiber cleaning and separation process further contributes to waste production in textile factories.